Willingness for change to new norm for traditional food business by SMEs entrepreneurs - Harifah Mohd Noor; Jurry Foo; Adilah Md Ramli; Teuku Afrizal Teuku Anuar (Universiti Teknologi MARA, 2021)
Traditional food represents the cultural identity that becomes an income source for Small and Midsize enterprises (SMEs) entrepreneurs in Sabah. The sudden presence of COVID-19 since March 2020 has impacted traditional food entrepreneurs. This research examines the readiness of entrepreneurs to innovate their businesses through a new norm. Factor Analysis is used to analyse 21 parameters of a new norm for the traditional food business. This study developed three dimensions: enhancing existing business, new norm business and improving business skills. Entrepreneurs need to prepare strategies to meet new business norms. Support from the government and agencies is required to enhance SME entrepreneurs' business capabilities.